Impact of a Modified Jigsaw Method for Learning an Unfamiliar, Complex Topic - Denise Kolanczyk; Sally A Arif (University of Minnesota Libraries Publishing, 2017)
Objective: The aim of this study was to use the jigsaw method with an unfamiliar, complex topic and to evaluate the effectiveness of the jigsaw teaching method on student learning of assigned material ("jigsaw expert") versus non-assigned material ("jigsaw learner"). Innovation: The innovation was implemented in an advanced cardiology elective. Forty students were assigned a pre-reading and one of four valvular heart disorders, a topic not previously taught in the curriculum. A pre-test and post-test evaluated overall student learning. Student performance on pre/post tests as the "jigsaw expert" and "jigsaw learner" was also compared. Critical Analysis: Overall, the post-test mean score of 85.75% was significantly higher than that of the pre-test score of 56.75% (p<0.05). There was significant improvement in scores regardless of whether the material was assigned ("jigsaw experts" pre=58.8% and post=82.5%; p<0.05) or not assigned ("jigsaw learners" pre= 56.25% and post= 86.56%, p<0.05) for pre-study. Next Steps: The use of the jigsaw method to teach unfamiliar, complex content helps students to become both teachers and active listeners, which are essential to the skills and professionalism of a health care provider. Further studies are needed to evaluate use of the jigsaw method to teach unfamiliar, complex content on long-term retention and to further examine the effects of expert vs. non-expert roles. Conflict of Interest We declare no conflicts of interest or financial interests that the authors or members of their immediate families have in any product or service discussed in the manuscript, including grants (pending or received), employment, gifts, stock holdings or options, honoraria, consultancies, expert testimony, patents and royalties.   Type: Note